HUBUNGAN KADAR GLUKOSA DARAH DENGAN PERTUMBUHAN A. actinomycetemcomitans PADA TIKUS DIABETES MELITUS - Tantin Ermawati (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Diabetes mellitus is a systemic disease characterized by insulin deficiency. Common symptoms in people with diabetes is elevated blood glucose is called hyperglycemia. Manifestations in the oral cavity are inflammation of gingival tissue or periodontitis. The bacteria that play a role in the severity of periodontal disease is A. actinomycetemcomitans. The purpose of this study was to determine the relationship of blood glucose levels with the growth of A. actinomycetemcomitans in DM rats treated with insulin therapy. Methode 20 three month old male Wistar rats with weight of 170-200 grams were divided into two groups. First, periodontitis and DM were manipulated into all groups through aloksan injection with dose of 170 mg/kg. Those rats in group I were treated with insulin, those in group II were without treatment. In the third and seventh weeks, the blood glucose levels and the number of A. actinomycetemcomitans was measured. The data was tested by using Pearson test. The results showed that there is a strong relationship between blood glucose levels with the growth of A. actinomycetemcomitans. Conclusion: The increasing blood glucose levels are very strongly associated with an increase in the number of A. actinomycetemcomitans and otherwise in DM rats with insulin therapy.